Representing Spanish Identity through españolada in Fernando Trueba's The Girl of your Dreams (La niña de tus ojos). - Hardcastle, Anne E. (Film Criticism)
The author comments on Fernando Trueba's film "The Girl of Your Dreams." He mentions that the film introduces its particular concern with the construction of Spanish identity through the españoladas it invokes. Numerous scenes of the film show stereotypical españolada fare such as passionate gypsies, flamenco dancers and bandoleros in rural 19th century Andalusia.